Sistem Informasi Sentra Pelayanan Kepolisian Terpadu (SPKT) Pada Polsek Lubuk Raja - Perdana, Meilyana Winda; Alfresi, Aminullah Imal; Ma’ruf, Muhammad Irvan (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
The Lubuk Raja Police and the Resort Police have functions, one of which is the Integrated Police Service Center (SPKT) whose role is to provide public services in the form of reporting from the community. In receiving reports from the public as well as when processing data, the SPKT Lubuk Raja Police officers still do it manually, such as when the officers make reports still using Microsoft Office, this can result in the accumulation of report files and make typing repeated every time there is a report from the public. In addition, there is still a manual for giving the register number and the process of recording the reporting data. Then, through a study at the Lubuk Raja Police at the Integrated Police Service Center (SPKT), the author thought about designing and creating a website-based information system. The system development method that the author uses in this study is the Waterfall Model which includes the steps of analyzing system requirements for code writing system design, testing, implementation, and maintenance. The "Software" software used in the creation of an integrated police service center information system (SPKT), such as: XAMPP (a "localhost" web server), MySQL (a SQL database management), Sublime text (as an editor, where we write program code) ). The final point of this research is the creation of an integrated police center information system (SPKT) to replace reporting, processing, and recording data, which previously used manual methods. With this, it will make it easier for members of the police to provide services to the community in the OKU police area